Detection of A Possible Subsurface Water Seepage Using 2D Electrical Resistivity Imaging Survey at a site in Al-Khwarizmi College of Engineering, University of Baghdad, Iraq - AL-Mahemmdi, Waleed D.; Al-Banna, Ahmed Sh.; AL-Menshed, Firas H. (Iraqi Journal of Science, 2023)
Unknown subsurface leaking water sources and possible subsurface seepage from a sewage tank in a garden at Al-Khawarizmi engineering college, University of Baghdad, were detected in this study. The 2D electrical resistivity imaging. The ERI survey is carried out along two lines, 60m and 50m long, with an electrode spacing of 1 m, forming a cross using the Wenner-Schlumberger array configuration. Line 1 is 60m, while line 2 is 50m. Soil samples were collected from line 1 at positions of electrode 34, which shows a high resistivity value, and electrode 55, which shows low resistivity, for laboratory analysis. Robust inversion and modelling processes showed relative change and high contrast in interpreted resistivities. Soil analysis showed a general homogeneity in mineral content and sediment type. Therefore, the relatively high contrast was related to variations in water content. The low resistivity was caused due to the water seepage from the sewage tank, which was precisely located.